2007
DOI: 10.1159/000112544
|View full text |Cite
|
Sign up to set email alerts
|

Poly-N-Acetyl Glucosamine Nanofibers Regulate Endothelial Cell Movement and Angiogenesis: Dependency on Integrin Activation of Ets1

Abstract: Poly-N-acetyl glucosamine (pGlcNAc) nanofiber-derived materials effectively achieve hemostasis during surgical procedures. Treatment of cutaneous wounds with pGlcNAc in a diabetic mouse animal model causes marked increases in cell proliferation and angiogenesis. We sought to understand the effect of the pGlcNAc fibers on primary endothelial cells (EC) in culture and found that pGlcNAc induces EC motility. Cell motility induced by pGlcNAc fibers is blocked by antibodies directed against αVβ3 and α Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 80 publications
2
29
0
Order By: Relevance
“…This effect is mediated by an induction of an integrin-dependent pathway [14]. We showed here that sNAG stimulation of HUVEC results in a marked increase in respiration in the absence of increased cell numbers.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This effect is mediated by an induction of an integrin-dependent pathway [14]. We showed here that sNAG stimulation of HUVEC results in a marked increase in respiration in the absence of increased cell numbers.…”
Section: Discussionmentioning
confidence: 62%
“…Recent findings show that the treatment of cutaneous wounds with sNAG-derived membranes results in increased kinetics of wound healing that can be attributed, in part, to a marked increase in angiogenesis [12,13]. We have shown that sNAG treatment stimulates wound integrin-dependent signaling pathways that result in increased endothelial cell motility [12,14]. Together these findings suggest that sNAGs promote wound healing and angiogenesis via the stimulation of outside-in integrin signal transduction.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…pGlcNAc nanofiber membranes increase cell metabolism and activate in vitro migration of endothelial and fibroblast cells. 13,26,27 In diabetic mouse studies, treatment of full-thickness wounds with pGlcNAc nanofiber membranes enhanced wound healing mainly by re-epithelialization and stimulation of angiogenesis, tissue remodeling, and endothelial cell proliferation. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different approaches have been tried for controlled drug release of VEGF. Beside the use as soluble factor or immobilized in fibrin hydrogels , VEGF can be bound to nanoparticles (des Rieux et al) or nanofibers (Vournakis et al 2008) as drug delivery systems (DDS) to improve angiogenesis in vivo (Zisch et al 2003). Kim et al have demonstrated the positive therapeutic effect of nanoparticle based VEGF release in ischemic muscle tissue (Kim, J. et al).…”
Section: Cell Survival In Vivo / Vascularizationmentioning
confidence: 99%